Importance of green areas for health in hospitals - Benavidez, Wildghem (Universidad Nacional de Ingeniería, 2019)
Always think of the garden as a purely playful place, such as a park or the simple garden of a hospital. It is very seldom thought about the healing power that ornamental plants can have, what effect do they have within a sanitary structure? Since the 1980s, the effects produced in patients have been studied and the positive results obtained have been scientifically proven. Its use is made every day more essential to lower costs and days of stay of patients in hospitals, and improve the quality of life of patients in structures where they need long-term care. The belief that plants and gardens are beneficial for patients goes back more than a thousand years and appears not only in Asian cultures but also in Western cultures. In the nineteenth century virtually all hospitals in America and Europe had gardens in their facilities. It is from the twentieth century when this trend is lost in favor of more sophisticated buildings created with the aim of reducing the risks of infection and adapt to new technologies.